Fatty Acid Accumulation and Resulting PPARα Activation in Fibroblasts due to Trifunctional Protein Deficiency - Masato Wakabayashi; Yuji Kamijo; Takero Nakajima; Naoki Tanaka; Eiko Sugiyama; Tian Yangyang; Takefumi Kimura; Toshifumi Aoyama (PPAR Research)
To examine fatty acid accumulation and its toxic effects in cells, we analyzed skin fibroblasts from six patients with mitochondrial trifunctional protein deficiency, who had abnormalities in the second through fourth reactions in fatty acid β-oxidation system. We found free fatty acid accumulation, enhanced three acyl-CoA dehydrogenases, catalyzing the first reaction in the β-oxidation system and being assumed to have normal activities in these patients, and PPARα activation that was confirmed in the experiments using MK886, a PPARα specific antagonist and fenofibrate, a PPARα specific agonist. These novel findings suggest that the fatty acid accumulation and the resulting PPARα activation are major causes of the increase in the β-oxidation ability as probable compensation for fatty acid metabolism in the patients’ fibroblasts, and that enhanced cell proliferation and increased oxidative stress due to the PPARα activation relate to the development of specific clinical features such as hypertrophic cardiomyopathy, slight hepatomegaly, and skeletal myopathy. Additionally, significant suppression of the PPARα activation by means of MK886 treatment is assumed to provide a new method of treating this deficiency.